Distribución espacial actual y futura de entomofauna benéfica (coccinella septempunctata), utilizando inaturalist como una herramienta para realizar registros de presencia, en la Región Sierra, 2023. - Unaucho Mañay, Alexandra Monserrath (2024)
The research aims to project the current and future distribution of Coccinella septempunctata in the Ecuadorian highland region, below two scenarios of time (2050 and 2080), based on alterations of climatic factors and presence data from citizen science platforms (INaturalist). The database for the work was elaborated with a total of 199 presence points in the entire study area. To improve the quality of the distribution models, bioclimatic layers were obtained from the World Clim platform with a resolution of 30 arc/sec each, and the most suitable layers were selected through Pearson's correlation index, indicating that 10 of the layers are the most optimal for the area. The MaxEnt program was used to analyze the database and the layers of current variables, resulting in greater influx of the species in Pichincha and Cotopaxi provinces, indicating that the average probability of the presence of Coccinella septempunctata is 8.68%, equivalent to 5207.234 km2, and in the high probability (PA) a resulting area of 3046.437 km2, equivalent to 5.08% of the total area. For the predictive models, the Global Circulation Models HADGEM3-ES and MIROC6 were used, under the climate projections ssp126 and ssp245 for both years, obtaining 8 distribution models for the future. The distribution models indicate an increase in the probabilities of medium and high presence in the area; and a reduction in the null probability with respect to the current distribution model. Likewise, when comparing the two time scenarios, it is evident that there is an increase in the probability of adaptation to the expected climate changes. It is necessary to emphasize that each model was validated with the ROC analysis and the AUC, where all show values higher than 0.89 indicating reliability in the results. A constant relationship between the climate factor and the dynamics of the potential distribution of the species is evident, i.e., if only the climatic factor of the region were taken into account, Coccinella septempunctata would extend its distribution ranges in the future and despite climate change the adaptability of this species is high.